A predictive framework for the reproducible seed-mediated synthesis and functionalization of gold nanorods - Brian Novati; Lucia Salvioni; Melissa Saibene; Alessandro Colombo; Roberto Lorenzi; Angelo Monguzzi; Stefania Garbujo; Miriam Colombo; Marco D. Giustra; Davide Prosperi (Chemical Engineering Journal, 2026)

Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Microclimate monitoring and modelling in a regenerating urban environment: Milano (Italy) - Luca Gallia; Stefano Basiricò; Shamila Haddad; Thomas Parkinson; Aysu Kuru; Akisha Nomoto; Roberto Colombo; Riccardo Castellanza; Federico Agliardi (Urban Climate, 2026)

Conversion of municipal biowaste into value-added products toward a circular bioeconomy: bridging the gap between laboratory-scale and full-scale implementation - José Manuel Alejandro Cerdán; Tatiana Kimura Kodama; G. H. D. Oliveira; Lucas Tadeu Fuess; Júlia Fonseca Colombo Andrade; Aldo Roberto Ometto (Clean Technologies and Environmental Policy, 2026)
Scaling-up municipal biowaste conversion technologies to industrial levels is essential for advancing clean and sustainable technologies and addressing significant technical, economic, and environmental challenges associated with urban organic waste management. Studies that explore technological gaps across the upstream, midstream, and downstream processing stages of biorefineries are critical for transforming biowaste into value-added products. This study aims to fill these gaps through a systematic literature review following the PRISMA guidelines and utilizing the Technology Readiness Level (TRL), which enabled the selection of 88 cases subsequently analyzed using descriptive and content analysis. The main findings show that anaerobic digestion has achieved full commercial maturity (TRL 9), while acidogenic fermentation remains mostly at TRL 6–7, and other pathways such as microbial protein or holocellulase production are still at early stages (TRL 3–4). High-value products, including polyhydroxyalkanoates (PHA) and succinic acid, are clustered at TRL 6–7, typically demonstrated at pilot scale, whereas hydrochar from hydrothermal carbonization has progressed up to TRL 8–9. Companies and projects confirm the feasibility of integrating biological, chemical, and thermal pathways into biorefineries, spanning a wide range of TRLs and showcasing their potential within the circular bioeconomy. Key gaps persist in scaling downstream processes for product purification, reducing costs, addressing feedstock variability, and optimizing pretreatment. By synthesizing experimental evidence with industrial demonstrations and sustainability assessments, this study provides a comprehensive perspective on how municipal biowaste can be converted into both non-fuel bioproducts and biofuels, thereby supporting circular bioeconomy strategies for future environmental policies. Graphical Abstract

Enhanced H2O2 electrogeneration for simultaneous degradation of multiple pharmaceuticals and validation in real water using UVC-assisted processes - Raul José Alves Felisardo; Florymar Escalona Durán; Carlos Henrique Magalhães Fernandes; Géssica de Oliveira Santiago Santos; Renata Colombo; Manuel Andrés Rodrigo Rodrigo; Marcos Roberto de Vasconcelos Lanza (Chemical Engineering Journal, 2026)

Single-cell protein meal produced from Methylovorus menthalis (Psomi™) in extruded aquafeeds for seawater phase Atlantic salmon (Salmo salar L.): Impacts on growth performance, nutrient utilization, fish health, and fillet quality - Sean M. Tibbetts; André Dumas; Van Pham Thi Ha To; Ivan Tankovski; Noppawan Chimsung; Shane J.J. Patelakis; Stefanie M. Colombo; Talia Boates; Roberto E. Armenta; Brianna Orr Stratton (Aquaculture, 2026)

Cathodic photoelectrocatalytic amitriptyline removal: Mechanistic insights into oxygen reduction reaction pathways upon influence of Ti, Zr and Hf selenide-modified gas diffusion electrodes - Fausto Eduardo Bimbi Júnior; Enric Brillas; Oswaldo Costa Junior; Kenneth Flores; Robson da Silva Souto; Caio Machado Fernandes; Renata Colombo; Willyam Roger Padilha Barros; Mauro Coelho dos Santos; Marcos Roberto de Vasconcelos Lanza; Sergi Garcia-Segura (Chemical Engineering Journal, 2026)

Late-phase depolarization and repolarization abnormalities in english bulldogs with phenotypic expression of arrhythmogenic cardiomyopathy - Mara Bagardi; Manuela Perego; Fabio M. Colombo; Alessandra Maffei; Paola G. Brambilla; Michele Polli; Giorgio Camozzini; Roberto A. Santilli (Veterinary Research Communications, 2025)

Hybrid Gaussian mixture model and unscented transformation algorithm for uncertainty propagation within the PUZZLE software - Roberto Detomaso; Andrea Muciaccia; Camilla Colombo (Advances in Space Research, 2025)

Immunization thresholds to change the overall level and the effect of cases on deaths by COVID-19 in pregnant and postpartum women - Alessandro José Queiroz Sarnaglia; Luciana Graziela de Godoi; Nátaly Adriana Jiménez Monroy; Fabio Alexander Fajardo Molinares; Bartolomeu Zamprogno; Diego Roberto Colombo Dias; Agatha Sacramento Rodrigues (Environmental Research, 2025)

Sustainable photocatalytic degradation of antibiotic norfloxacin using microfibrillated cellulose@ZnO nanocomposites - Ramon Resende Leite; Renata Colombo; Ailton José Moreira; Júlia Mendes Farias; Fausto Eduardo Bimbi Júnior; Juliana Bruzaca Lima; Marcos Roberto de Vasconcelos Lanza; Hernane da Silva Barud; Maria Inês Basso Bernardi (Chemosphere, 2024)

Seropositivity for Toxoplasma gondii in cats with clinical signs and living in households with women of childbearing age - Donato Traversa; Simone Morelli; Angela Di Cesare; Mariasole Colombo; Raffaella Iorio; Alessandra Pagliaccia; Cecilia Catalano; Barbara Paoletti; Roberto Brueckmann (Veterinary Parasitology, 2024)

Disruption of exploratory behavior and olfactory memory in cockroaches exposed to sublethal doses of the neonicotinoid Thiamethoxam - Letícia Campos Ferreira; Maria Eduarda Rosa; Luis Guilherme Silva Rodrigues; Diego Roberto Colombo Dias; Marcelo de Paiva Guimarães; Chiara Valsecchi; Velci Queiroz de Souza; Renata de Faria Barbosa; Lucia Helena Vinadé; Stephen Hyslop; João Batista Teixeira da Rocha; Cháriston André Dal Belo (Pesticide Biochemistry and Physiology, 2024)

Residues of agrochemicals in beebread as an indicator of landscape management - Gherardo Bogo; Valeria Caringi; Sergio Albertazzi; Vittorio Capano; Roberto Colombo; Amanda Dettori; Irene Guerra; Giulia Lora; Laura Bortolotti; Piotr Medrzycki (Science of The Total Environment, 2024)

Pigmented corn as a gluten-free source of polyphenols with anti-inflammatory and antioxidant properties in CaCo-2 cells - Stefano Piazza; Corinne Bani; Francesca Colombo; Francesca Mercogliano; Carola Pozzoli; Giulia Martinelli; Katia Petroni; Salvatore Roberto Pilu; Elisa Sonzogni; Marco Fumagalli; Enrico Sangiovanni; Patrizia Restani; et al. (Food Research International, 2024)

Precursor effect on the hydrothermal synthesis of pure ZnO nanostructures and enhanced photocatalytic performance for norfloxacin degradation - Ramon Resende Leite; Renata Colombo; Fausto Eduardo Bimbi Júnior; Marcos Roberto de Vasconcelos Lanza; Hernane da Silva Barud; Conrado Ramos Moreira Afonso; Maria Inês Basso Bernardi (Chemical Engineering Journal, 2024)

Degradation of diethyl phthalate by photolysis of hydrogen peroxide electrogenerated using a Printex L6 carbon modified with Benzophenone cathode in an improved tangential flow cell - Taynara Oliveira Silva; Géssica de Oliveira Santiago Santos; Renata Colombo; Marcos Roberto de Vasconcelos Lanza; Manuel Andrés Rodrigo Rodrigo (Process Safety and Environmental Protection, 2024)

Sulfamerazine degradation employing a novel Z-scheme TiO2/KNbO3/g-C3N4 photocatalyst under artificial sunlight: Insights on degradation mechanism and toxicity - Nicolas Perciani de Moraes; Tiago Moreira Bastos Campos; Gilmar Patrocínio Thim; Yu Lianqing; Robson da Silva Rocha; Renata Colombo; Liana Alvares Rodrigues; Marcos Roberto de Vasconcelos Lanza (Journal of Environmental Chemical Engineering, 2024)

Influence of soil - foundation - tank interaction on buckling strength of liquid storage tanks - Juan Ulloa-Rojas; José Colombo; José Wilches; Roberto León; José Almazán (Engineering Structures, 2024)

Towards a standardized, ground-based network of hyperspectral measurements: Combining time series from autonomous field spectrometers with Sentinel-2 - Paul Naethe; Andrea De Sanctis; Andreas Burkart; Petya K.E. Campbell; Roberto Colombo; Biagio Di Mauro; Alexander Damm; Tarek El-Madany; Francesco Fava; John A. Gamon; Karl F. Huemmrich; Mirco Migliavacca; et al. (Remote Sensing of Environment, 2024)

Radar observation and recontruction of Cosmos 1408 fragmentation - Andrea Muciaccia; Luca Facchini; Marco Felice Montaruli; Giovanni Purpura; Roberto Detomaso; Camilla Colombo; Mauro Massari; Pierluigi Di Lizia; Alessandra Di Cecco; Luca Salotti; Germano Bianchi (Journal of Space Safety Engineering, 2024)

Sun-induced fluorescence spectrum as a tool for assessing peatland vegetation productivity in the framework of warming and reduced precipitation experiment - Michal Antala; Anshu Rastogi; Sergio Cogliati; Marcin Stróżecki; Roberto Colombo; Radosław Juszczak (Remote Sensing of Environment, 2024)

A deep scalable neural architecture for soil properties estimation from spectral information - Flavio Piccoli; Micol Rossini; Roberto Colombo; Raimondo Schettini; Paolo Napoletano (Computers & Geosciences, 2023)

Exposure to secondhand and thirdhand smoke in private vehicles: Measurements in air and dust samples - Xavier Continente; Elisabet Henderson; Laura López-González; Esteve Fernández; Olena Tigova; Sean Semple; Rachel O'Donnell; Ana Navas-Acién; Núria Cortés-Francisco; Noelia Ramírez; Ruaraidh Dobson; Maria José López; et al. (Environmental Research, 2023)

Empirical insights on the use of sun-induced chlorophyll fluorescence to estimate short-term changes in crop transpiration under controlled water limitation - Kazi Rifat Ahmed; Eugenie Paul-Limoges; Uwe Rascher; Jan Hanus; Franco Miglietta; Roberto Colombo; Alessandro Peressotti; Andrea Genangeli; Alexander Damm (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Quantitative Evaluation of the Fracturing State of Crystalline Rocks Using Infrared Thermography - Federico Franzosi; Stefano Casiraghi; Roberto Colombo; Chiara Crippa; Federico Agliardi (Rock Mechanics and Rock Engineering, 2023)
The fracturing state of rocks is a fundamental control on their hydro-mechanical properties. It can be quantified in the laboratory by non-destructive geophysical techniques that are hardly applicable in situ, where biased mapping and statistical sampling strategies are usually exploited. We explore the suitabilty of infrared thermography (IRT) to develop a quantitative, physics-based approach to predict rock fracturing starting from laboratory scales and conditions. To this aim, we performed an experimental study on the cooling behaviour of pre-fractured gneiss and mica schist samples, whose 3D fracture networks were reconstructed using Micro-CT and quantified by unbiased fracture abundance measures. We carried out cooling experiments in both controlled (laboratory) and natural (outdoor) environmental conditions and monitored temperature with a thermal camera. We extracted multi-temporal thermograms to reconstruct the spatial patterns and time histories of temperature during cooling. Their synthetic description show statistically significant correlations with fracture abundance measures. More intensely fractured rocks cool at faster rates and outdoor experiments show that differences in thermal response can be detected even in natural environmental conditions. 3D FEM models reproducing laboratory experiments outline the fundamental control of fracture pattern and convective boundary conditions on cooling dynamics. Based on a lumped capacitance approach, we provided a synthetic description of cooling curves in terms of a Curve Shape Parameter, independent on absolute thermal boundary conditions and lithology. This provides a starting point toward the development of a quantitative methodology for the contactless in situ assessment of rock mass fracturing.

Cardiorespiratory coupling in mechanically ventilated patients studied via synchrogram analysis - Davide Ottolina; Beatrice Cairo; Tommaso Fossali; Claudio Mazzucco; Antonio Castelli; Roberto Rech; Emanuele Catena; Alberto Porta; Riccardo Colombo (Medical & Biological Engineering & Computing, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

High spatial resolution solar-induced chlorophyll fluorescence and its relation to rainfall precipitation across Brazilian ecosystems - Luis Miguel da Costa; Gislaine Costa de Mendonça; Gustavo André de Araújo Santos; José Reinaldo da Silva Cabral de Moraes; Roberto Colombo; Alan Rodrigo Panosso; Newton La Scala Jr. (Environmental Research, 2023)

Mapping snow density through thermal inertia observations - Roberto Colombo; Greta Pennati; Giulia Pozzi; Roberto Garzonio; Biagio Di Mauro; Claudia Giardino; Sergio Cogliati; Micol Rossini; Antonino Maltese; Paolo Pogliotti; Edoardo Cremonese (Remote Sensing of Environment, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Characterization of “Mais delle Fiorine” (Zea mays L.) and nutritional, morphometric and genetic comparison with other maize landraces of Lombardy region (Northern Italy) - Luca Giupponi; Valeria Leoni; Federico Colombo; Elena Cassani; Monika Hejna; Luciana Rossi; Roberto Pilu (Genetic Resources and Crop Evolution, 2021)
The loss of agrobiodiversity is a topic of global impact. On a local scale, Lombardy, in the Alpine macro-Region, has lost more than 78% of its plant agrobiodiversity. Only four maize ( Zea mays L. subsp. mays ) landraces of Lombardy are registered in the European Register of Conservation Varieties. However, there are other maize landraces in Lombardy such as “Mais delle Fiorine”, which was characterized from an agronomic, morphometric, nutritional and genetic point of view in this research and then compared with the four other landraces already registered (“Spinato di Gandino”, “Rostrato Rosso di Rovetta”, “Scagliolo di Carenno” and “Nero Spinoso”). “Mais delle Fiorine” resulted richer in starch (81% ± 1.6) and zinc (35.8 ± 9.1 mg Kg −1 ) and lower in phosphorus (3256.7 ± 204.2 mg Kg −1 ). The kernels in the five landraces also differ in the mean shape that is obovate without beak. A genetic distinction between “Mais delle Fiorine” and the other varieties was observed, and in particular compared to “Nero Spinoso”, while “Scagliolo di Carenno” and “Rostrato Rosso di Rovetta” showed great similarities. As regards agronomical trials, “Mais delle Fiorine” can grow from the Po Valley (90 m a.s.l.) to the mountain environments of the Seriana Valley (also over 900 m a.s.l.) without significant differences in grain yield. In addition, this landrace would seem able to tolerate environments where there is a greater probability of water stress.

Bioindicators and biomonitoring: honeybees and hive products as pollution impact assessment tools for the Mediterranean area - Stefano Girotti; Severino Ghini; Elida Ferri; Luca Bolelli; Roberto Colombo; Giorgia Serra; Claudio Porrini; Stefano Sangiorgi (Euro-Mediterranean Journal for Environmental Integration, 2020)
The global range of the environmental quality issues we all face necessitates integrated action from all of the countries that suffer from a particular environmental issue. We must be able to obtain data on the presence of pollutants and their effects on biota from any territory, regardless of its environmental, infrastructural, social, and economic conditions. Biomonitoring utilizes organisms and natural materials to obtain this information. In particular, the honeybee is a ubiquitous, easy-to-breed organism with great mobility. Its body, which is covered with hairs, picks up materials and particulates that it encounters in the environment. Therefore, bees are highly effective accumulators of materials from the soil, vegetation, air, and water. These characteristics mean that the honeybee is both a bioindicator and a passive bioaccumulator organism, making it an ideal agent for easily monitoring vast areas inexpensively, even in regions where infrastructure is scarce. In this short review, we summarize the main targets of the honeybee-based monitoring campaigns that have been carried out to date, highlighting the results obtained in assessments of organic and inorganic pollution performed by coupling more modern technologies with this long-standing practice. It is hoped that this review will make scientists more aware of the incredible potential of these delicate organisms to provide data that could prove useful in the management of environmental issues.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

Effects of Pesticides and Electromagnetic Fields on Honeybees: A Field Study Using Biomarkers - Daniela Lupi; Paolo Tremolada; Mario Colombo; Roberto Giacchini; Roberto Benocci; Paolo Parenti; Marco Parolini; Giovanni Zambon; Marco Vighi (International Journal of Environmental Research, 2020)

Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

The patterns and possible causes of global geographical variation in the body size of the greater horseshoe bat ( Rhinolophus ferrumequinum ) - Tinglei Jiang; Jing Wang; Hui Wu; Gabor Csorba; Sébastien J. Puechmaille; Petr Benda; Josselin Boireau; Roberto Toffoli; Jean‐Yves Courtois; Pierrette Nyssen; Raphael Colombo; Jiang Feng (Journal of Biogeography, 2019)
Aim Geographical variations in endotherm body size (e.g. Bergmann's rule/James's rule and Allen's rule) have long been tested. However, the patterns and causes of geographical variation in body size within bat species, especially within widespread hibernating species, are little known. Here, we evaluated the possible causes of geographical size variation patterns in the greater horseshoe bat ( Rhinolophus ferrumequinum ), a bat species widely distributed across the Palearctic. Location Palearctic. Methods We collected body size data (body mass and forearm length) from 1,172 adult bats via direct measurements or from the literature. We used high‐resolution environmental data for the sampled sites. We applied multiple linear regressions and an information‐theoretic approach on separate female and male datasets to estimate the support for various hypotheses. Results Temperature and latitude failed to predict body mass in both females and males. The best model showed that populations with longer forearms in both sexes were associated with higher mean temperatures (in the warmest quarter) and lower mean temperatures (in the coldest quarter). The independent contribution of these temperature parameters to forearm length in both sexes was higher than that of all other variables. Main conclusion The observed relationship between temperature and body mass was not consistent with James's rule, and thus failed to support the heat conservation hypothesis. Our results are consistent with the predictions of Allen's rule and indicated that direct heat dissipation from the wing may be the most likely mechanism underlying geographical variation in forearm length. We suggest that the evaluation of the relative importance of multiple causal mechanisms may improve our understanding of patterns of geographical variation in endotherms.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Trans-splicing of plastid rps12 transcripts, mediated by AtPPR4, is essential for embryo patterning in Arabidopsis thaliana - Luca Tadini; Roberto Ferrari; Marie-Kristin Lehniger; Chiara Mizzotti; Fabio Moratti; Francesca Resentini; Monica Colombo; Alex Costa; Simona Masiero; Paolo Pesaresi (Planta, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Classifying zones of suitability for manual drilling using textural and hydraulic parameters of shallow aquifers: a case study in northwestern Senegal - F. Fabio Fussi; Letizia Fumagalli; Francesco Fava; Biagio Di Mauro; Cheik Hamidou Kane; Magatte Niang; Souleye Wade; Barry Hamidou; Roberto Colombo; Tullia Bonomi (Hydrogeology Journal, 2017)

JC virus urinary excretion and seroprevalence in natalizumab-treated multiple sclerosis patients - Serena Delbue; Francesca Elia; Camilla Carloni; Valentina Pecchenini; Diego Franciotta; Matteo Gastaldi; Elena Colombo; Lucia Signorini; Silvia Carluccio; Anna Bellizzi; Roberto Bergamaschi; Pasquale Ferrante (Journal of NeuroVirology, 2015)

Models to predict the start of the airborne pollen season - Consolata Siniscalco; Rosanna Caramiello; Mirco Migliavacca; Lorenzo Busetto; Luca Mercalli; Roberto Colombo; Andrew D. Richardson (International Journal of Biometeorology, 2015)

Timing of multiple hydrothermal events in the iron oxide–copper–gold deposits of the Southern Copper Belt, Carajás Province, Brazil - Carolina P. N. Moreto; Lena V. S. Monteiro; Roberto P. Xavier; Robert A. Creaser; S. Andrew DuFrane; Gustavo H. C. Melo; Marco A. Delinardo da Silva; Colombo C. G. Tassinari; Kei Sato (Mineralium Deposita, 2015)

Validation of FreeSurfer-Estimated Brain Cortical Thickness: Comparison with Histologic Measurements - Francesco Cardinale; Giuseppa Chinnici; Manuela Bramerio; Roberto Mai; Ivana Sartori; Massimo Cossu; Giorgio Lo Russo; Laura Castana; Nadia Colombo; Chiara Caborni; Elena De Momi; Giancarlo Ferrigno (Neuroinformatics, 2014)

Review on iron availability in soil: interaction of Fe minerals, plants, and microbes - Claudio Colombo; Giuseppe Palumbo; Ji-Zheng He; Roberto Pinton; Stefano Cesco (Journal of Soils and Sediments, 2014)

Chlorophyll concentration mapping with MIVIS data to assess crown discoloration in the Ticino Park oak forest - Cinzia Panigada; Micol Rossini; Lorenzo Busetto; Michele Meroni; Francesco Fava; Roberto Colombo (International Journal of Remote Sensing, 2010)

First lead isotopic data for cinnabar in the Almadén district (Spain): implications for the genesis of the mercury deposits - Pablo Higueras; José Munhá; Roberto Oyarzun; Colombo C. G. Tassinari; Izabel R. Ruiz (Mineralium Deposita, 2005)

Origin and spread of the 1278insTATC mutation causing Tay-Sachs disease in Ashkenazi Jews: genetic drift as a robust and parsimonious hypothesis - Amos Frisch; Roberto Colombo; Elena Michaelovsky; Mazal Karpati; Boleslaw Goldman; Leah Peleg (Human Genetics, 2004)

Age and origin of the FCMD 3′-untranslated-region retrotransposal insertion mutation causing Fukuyama-type congenital muscular dystrophy in the Japanese population - Roberto Colombo; Angelo A. Bignamini; Anna Carobene; Junko Sasaki; Masashi Tachikawa; Kazuhiro Kobayashi; Tatsushi Toda (Human Genetics, 2000)

Age of the intronic GAA triplet repeat expansion mutation in Friedreich ataxia - Roberto Colombo; Anna Carobene (Human Genetics, 2000)

S-NO-actin: S-nitrosylation kinetics and the effect on isolated vascular smooth muscle - Isabella Dalle-donne; Aldo Milzani/snm>; Daniela Giustarini; Paolo Di Simplicio; Roberto Colombo; Ranieri Rossi (Journal of Muscle Research and Cell Motility, 2000)

Antidepressant-like effect of ethanol revealed in the forced swimming test in Sardinian alcohol-preferring rats - Roberto Ciccocioppo; Izabela Panocka; Rino Froldi; Giancarlo Colombo; Gian Luigi Gessa; M. Massi (Psychopharmacology, 1999)